KAJIAN PERBANDINGAN PENYEDERHANAAN BIROKRASI PADA JABATAN ADMINISTRASI KE JABATAN FUNGSIONAL PEMERINTAHAN NEGARA INDONESIA DENGAN PEMERINTAHAN NEGARA SINGAPURA - Oktavianus, Afriman (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Simplification of Bureaucracy in Administrative Positions to Functional Positions or more often known by other terms, namely "Equalization of Positions" in Indonesia is a consequence of changes in the legal, political, economic and social order. Identify problems as the focus of discussion, namely How to Equalize administrative positions into functional positions in Indonesia, and How to equalize administrative positions into functional positions in Singapore and compared to the application in Indonesia. The author’s purpose in conducting this study is to find out the equalization of administrative positions into functional positions in Indonesia, and to know, and study the equalization of administrative positions into functional positions in Singapore, and compared to the application in Indonesia. The concept of equalizing administrative positions into functional positions has several advantages compared to the old system which was only based on administrative positions. While the Civil Service Career Scheme (CSCS) in Singapore has many advantages, such as providing clear and structured career paths for civil servants, there are also some negative impacts to note. The conclusion that equalization of positions is an effort to improve personnel governance in a government agency. Suggestions, there needs to be commitment and consistency from all relevant parties in the implementation of equalization of positions in Indonesia